The warm-up maximize performance and improve long-term athletic development - Jeffreys, Ian (Champaign, Illinois Human Kinetics, 2019)
This book guides strength and conditioning professionals, personal trainers, and coaches through the process of constructing effective RAMP-based warm-ups. The RAMP protocol (Raise; Activate and Mobilize; and Potentiate) is a systems approach that ensures each element of the warm-up contributes positively to the next, allowing the whole to be far greater than the component parts. Unlike traditional warm-ups, the RAMP protocol considers the medium and longer-term development of the athlete. The book describes the science of the warm-up and provides guidelines for the practitioner to follow to maximize the effectiveness of the warm-up
Why we warm up -- The need for a new way of thinking about the warm-up -- The RAMP system of warming up -- The raise phase -- The activation and mobilization phase -- The potentiation phase -- Constructing effective warm-ups
Includes bibliographical references and index
Keywords: Exercise; Physical fitness